Atypical teratoid rhabdoid brain tumor in an infant with ring chromosome 22 - Eun Hae Cho; Jae Bok Park; Jin Kyung Kim (Korean Pediatric Society, 2014)
Reports of constitutional ring chromosome 22, r(22) are rare. Individuals with r(22) present similar features as those with the 22q13 deletion syndrome. The instability in the ring chromosome contributes to the development of variable phenotypes. Central nervous system (CNS) atypical teratoid rhabdoid tumors (ATRTs) are rare, highly malignant tumors, primarily occurring in young children below 3 years of age. The majority of ATRT cases display genetic alterations of SMARCB1 (INI1/hSNF5), a tumor suppressor gene located on 22q11.2. The coexistence of a CNS ATRT in a child with a r(22) is rare. We present a case of a 4-month-old boy with 46,XY,r(22)(p13q13.3), generalized hypotonia and delayed development. High-resolution microarray analysis revealed a 3.5-Mb deletion at 22q13.31q13.33. At 11 months, the patient had an ATRT (5.6 cm×5.0 cm×7.6 cm) in the cerebellar vermis, which was detected in the brain via magnetic resonance imaging.